Gastric Pneumatosis in the Setting of Diabetic Ketoacidosis - Mohammed Rifat Shaik; Chet Ranabhat; Nishat Anjum Shaik; Akshay Duddu; Zaid Bilgrami; Guofeng Xie (Case Reports in Gastrointestinal Medicine)
Gastric pneumatosis, an uncommon radiologic finding characterized by the presence of gas within the gastric wall, presents a diagnostic challenge due to its association with both benign gastric emphysema and more severe emphysematous gastritis. The contrasting outcomes and management approaches for these conditions underscore the necessity for accurate diagnosis and appropriate intervention. We present a case of a 29-year-old female with a medical history significant for type 1 diabetes mellitus who presented with abdominal pain, nausea, and vomiting. Initial evaluation revealed elevated blood glucose levels, an anion gap metabolic acidosis, and evidence of gastric pneumatosis on imaging. The patient was managed with aggressive fluid resuscitation and intravenous insulin therapy per diabetic ketoacidosis protocol. General surgery evaluation ruled out the need for acute surgical intervention and attributed the gastric pneumatosis to increased intragastric pressures from prolonged vomiting. The patient was managed with conservative measures, including nasogastric tube decompression and antibiotics. Over the course of a few days, the patient showed signs of clinical and radiologic improvement, with a resolution of symptoms. This case highlights the importance of accurate diagnosis and appropriate management strategies tailored to the underlying pathology to optimize patient outcomes in cases of gastric pneumatosis.